Technology-enhanced learning (TEL) of Karnaugh map - Mohamed Syafiq Mohamed Shah (2018)
This project serves to provide an alternative platform for users dealing with Karnaugh Map (K-Map) by developing a Technology-Enhanced Learning (TEL) software program of K-Map in order to assist users in strengthening solving abilities and concepts of K-Map. This platform was developed specifically to improve the traditional learning methods by incorporating and utilising current technology.